Depresión y su repercusión en el ámbito interpersonal en un paciente de 58 años - Macias Zurita, Everlin Valeria (2019)
Depression is a disease that makes it impossible for the individual to perform their daily activities, it is associated with patients with chronic or terminal diseases, as it is in the case presented, it is associated with the renal insufficiency that has been suffering for several years, that has deteriorated his physical state, and self-esteem having as consequence the emergence of avoidant behaviors, which was causing a serious affectation in the interpersonal environment. The diagnostic tests, the Avoidance Scale and Social Anguish of Watson and Friend Yesavage geriatric depression scale, the clinical history and the observation guide were very useful, the diagnosis of depression could be established, the established therapeutic scheme used the model Cognitive behavioral, the use of these techniques yielded good results, improving the interpersonal relationships of the patient and reducing the avoidance and escape behaviors